A wait-list controlled evaluation of the Qhubeka bicycle on an adolescent's physiology, executive function, and school performance - Mcdonald, Reece Brian (Department of Human Biology, 2022)
Learner mobility and active school travel (AST) has been proposed to improve school attendance and academic performance. In South Africa, approximately 86% of learners have been reported as walking to and from school. AST in Africa is becoming less common in urban areas, and this may be a contributing factor to the increased risk and frequency of noncommunicable diseases due to decreased physical activity. The aim of this wait-list controlled evaluation was to assess the physiological and cognitive changes of access to a bicycle versus walking on adolescents. Specifically, changes adolescent's physical activity levels and executive function in a South African low-income community. Two schools were recruited, with the evaluation school receiving bicycles and the control a school who were yet to receive bicycles. Significant differences were observed across the physiological and executive function assessments. Most notably in the executive function tests, the evaluation group showed significant time to completion decreases across all three tests (N-Back, Arrow Flanker, WCST: p< 0.001). The results from this study are significant, as they are the first to assess anthropometric, physiological and executive function in South African adolescents from low-socioeconomic regions. It is evident that there are potential improvements in working memory, inhibition and shifting due to cycling as a mode of AST or during leisuretime. Further research needs to determine the specific mechanisms associated with these improvements.